Perceived Use, Satisfaction Level and Benefits among Student Library Users of a Higher Education Institution in Isabela Province, Philippines - D. Dagdag, Januard; C. Galiza, Clarinda (International Journal of Psychosocial Rehabilitation, 2020)
The advent of artificial intelligence, accreditation, standardization, and employment competition demands school libraries to be competitive in meeting the fast-changing radical academic needs of clienteles. This descriptive research assesses the perceived library use, level of satisfaction, and benefits of 197 students of a higher education institution in Isabela, Philippines. Most of the students use the library weekly or twice in a month to do assignments, read lessons in advance, and borrow/return books. The library materials the majority used were books and dictionaries, while only 1 in every 5 students used the computers. The patronizing of books is associated with their perceived dissatisfaction with available internet connectivity for downloading e-books and fast-tracking information searches. They strongly agree that using the library enables them to become efficient in their studies, especially in their assignments, written projects, and examinations. One-way analysis of variance revealed that the students who used the library more frequently claimed more library benefits. Hence, the research suggests the importance of internet connectivity that satisfies the needs of the library clients in terms of fast and comprehensive information search; regular needs analysis of reference books for updating before the semester begins; and maximizing library use to get the best and most fulfilling library experience.